Chasing after Non-cyanobacterial Nitrogen Fixation in Marine Pelagic Environments - Moisander, Pia H.; Benavides, Mar; Bonnet, Sophie; Berman-Frank, Ilana; White, Angelicque E.; Riemann, Lasse (Frontiers in Microbiology, 2017)
Traditionally, cyanobacterial activity in oceanic photic layers was considered responsible for the marine pelagic dinitrogen (N2) fixation. Other potentially N2-fixing bacteria and archaea have also been detected in the pelagic water column, however, the activity and importance of these non-cyanobacterial diazotrophs (NCDs) remain poorly constrained. In this perspective we summarize the N2 fixation rates from recently published studies on photic and aphotic layers that have been attributed to NCD activity via parallel molecular measurements, and discuss the status, challenges, and data gaps in estimating NCNF in the ocean. Rates attributed to NCNF have generally been near the detection limit thus far (<1 nmol N L-1 d-1). Yet, if considering the large volume of the dark ocean, even low rates of non-cyanobacterial N2 fixation (NCNF) could make a significant contribution to the new nitrogen input to the ocean. The synthesis here shows that nifH transcription data for NCDs have been reported in only very few studies where N2 fixation rates were reported in the absence of diazotrophic cyanobacteria. In addition, high apparent diversity and regional variability in the NCDs complicate investigations of these communities. Future studies should focus on further investigating impacts of environmental drivers including oxygen, dissolved organic matter, and dissolved inorganic nitrogen on NCNF. Describing the ecology of NCDs and accurately measuring NCNF rates, are critical for a future evaluation of the contribution of NCNF to the marine nitrogen budget.